Polarisation of Policy Responses to COVID-19 Among ASEAN Countries = Polarização das Respostas Políticas ao COVID-19 entre os Países da ASEAN - Sonia Kumari, Selvarajan; Rossazana, Ab Rahim (Associação Portuguesa para o Desenvolvimento Regional (APDR), 2023)
COVID-19 pandemic effects are heterogenous in nature due to the differences in policy responses among the nations, with no exception to Association of Southeast Asian Nations (ASEAN). COVID19 responses undertaken by individual member countries of ASEAN have been tremendously diverse and have ranged from strict lockdown conditions in the highly regulated city-state of Singapore to ‘business as usual’, especially in rural areas of developing countries with large informal economies such as Laos and Myanmar. Studies on the nexus between concerted regional effort and the consequences of the pandemic appear to be limited; thus, this study aims to investigate the polarisation of the policy responses among the individual ASEAN countries. Examining the polarisation trend offers an insight on the responses of the nation towards handling the COVID-19 pandemic. This study employs Philips and Sul method to test the convergence of the polarisation of ASEAN countries.